Frequency of significant steatosis in various chronic liver diseases: an evaluation with Transient Elastography (TE) - Shahrani, Shahreedhan; balakrishnan, Preetica mayuri; ravi, Koshni; singh, sandeep; chee, sher wye; zulkeflie, saiful hasyim; ng, ying zhuang; lee, wai kin; AK, Mohamed amin; Sooi, Choong Yeong; CK, vikneshwaran; Nik Muhamad Affendi, Nik Arsyad; et al. (2022)
INTRODUCTION: TE was developed as a non-invasive method to assess liver fibrosis and steatosis using shear wave velocity. Many studies have proven its’ effectiveness as a method for evaluating liver fibrosis and steatosis.1-2 OBJECTIVE: To determine the prevalence and aetiology of steatosis in our local population. METHOD: This study was conducted as a retrospective review on all patients who had TE performed at UMMC from 1 January 2013 to 31 December 2021. Their demographics, clinical characteristics and TE findings were charted. RESULTS: A total of 3066 patients were included. 51.7% were males and 48.3% were females. The median CAP value was 271 dB/m. The median E value was 6.5kPa. 61.2% of patients had steatosis, with a staggering number of of these patients having significant steatosis (51.8%). 6.3% of patients had S2 steatosis whereas 45.5% of patients had severe (S3) steatosis. Interestingly, in those with S2 steatosis, 34.7% had chronic hepatitis B (CHB), 31.5% had non-alcoholic fatty liver disease (NAFLD), 5.2% with chronic hepatitis C (CHC) and 1% had alcoholic liver disease (ALD). In the S3 steatosis group, 66.7% had NAFLD, followed by ALD (36.6%), CHB (30.1%) and CHC (27.7%). 221